World Scientific Encyclopedia of Business Sustainability, Ethics and Entrepreneurship : Vol1: environmental and social entrepreneurship, Vol2: sustainable development goals, Vol3: spirituality, entrepreneurship and social change - Markman, Gideon D. (Hackensack: London: World Scientific Publishing, 2022)
"Volume 1: This volume is the culmination of many discussions among the editors over the years, especially at the Sustainability, Ethics and Entrepreneurship (SEE) Conference, related to the growth and institutionalization of environmental and social entrepreneurship. Research on these two forms of entrepreneurial action has tried to keep pace with what is occurring in the field. While the research is diverse, attracting scholars across many disciplines and from all parts of the world, it is still in the formative stages. This volume seeks to take stock of the literature and report the state of the art in environmental and social entrepreneurship. In particular, it seeks to explore new theoretical directions that blend traditional notions of economic efficiency and social welfare and new ways of measuring and empirically testing these phenomena. The chapters in this volume demonstrate the diverse philosophical, methodological, and theoretical techniques to studying these forms of entrepreneurship. We expect this volume will contribute to this burgeoning research and that researchers will engage in theory development for the foreseeable future, as new business models are developed, tested, abandoned, and evolved. Volume 2: This volume spotlights cutting-edge research, innovative methodologies, and provocative thinking by organizational scholars and leaders committed to advancing the global sustainability agenda. Each chapter focuses on advancing one or more United Nations (UN) 2030 Sustainable Development Goals (SDGs). The chapter sequence follows a general logic of SDG numerical order and breadth. Overall, this compendium provides critical insights, practical strategies and tools, and timely inspiration to motivate individual and collective engagement with and achievement of the SDGs. With a decade remaining to achieve the 2030 Agenda, this volume supports sustainable development globally, through: identification of key challenges; theoretical, empirical, and practical exploration of potential solutions; and sharing of actionable findings. Each chapter makes an impactful contribution by spotlighting opportunities for advancing best-in-class efforts toward the achievement of the SDGs. Chapters represent diverse scholarly perspectives and include a representative range of focal SDGs, organizational contexts, applications, and initiatives from Africa, Asia, Europe, North and South America, and spanning national borders. Volume 3: Historically religious institutions have been at the forefront of social change, yet religion and spirituality are rarely discussed in contemporary entrepreneurship research. We challenge this oversight and argue that by ignoring the fundamental principles that define an overwhelming majority of people all over the world, our scholarship risks being partial, incomplete and thus misleading. This volume presents a selection of entrepreneurship perspectives - studies, essays and analyses - that integrate religion and spirituality with social change. We have deliberately sought chapters that are edgy and novel, to give different nuances on this integration of religion and spirituality with entrepreneurship for social change"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Sustainable development; Social entrepreneurship